Informatics, Computer Science Faculty, Bandar Lampung University - Triadi S; Vandika A Y (Bandar Lampung University (UBL), 2017)
According to the meaning literally, the image (image )is a two-dimensional image on the field. Judging from the mathematical point of view, the image is a continuous function (continue) the intensity of light in the two-dimensional plane. The light source illuminates an object, then the object reflects back a portion of the light beam. This light reflection is captured by optical devices, such as the human eye, a camera, scanner, and others so that the shadow of the object in the form of the image can be recorded (Sitorus, Syahriol, 2006). In scientific writing, the author analyzes on the detection of handwriting on a blackboard. Handwriting recognition is one area of pattern recognition and is a part of computer sciencefield Computervision and artificial intelligenceis being developed at this time.While the blackboard were planks of wood with a surface that can be rewritten by using markers. Chalkboard ancient times was made of a thin sheet of slate black or gray. Chalkboard is now made of sheets of thin boards painted with glossy paint, usually white. Whiteboards are commonly used in schools and educational institutions. With a variation of a wide variety of reasons. Chalkboard often unpopular student with written reasons lecturer on the board can not read, so difficult to understand.